Apple phlorizin oxidation product 2 inhibits proliferation and differentiation of 3T3-L1 preadipocytes. (November 2019) - Wang, Xue; Wang, Juan; Wei, Lina; Hu, Ching Yuan; Deng, Hong; Guo, Yurong; Meng, Yong Hong
Graphical abstract: Highlights: POP2 had higher radical scavenging activity than phlorizin. POP2 decreased adipocytes viability. POP2 reduced the accumulation of TG in the adipocytes. POP2 inhibited adipocytes differentiation. Abstract: Phlorizin is a natural polyphenol with many bioactivities, however, its low water solubility limits its application. Phlorizin oxidation product 2 (POP2) has higher water solubility than phlorizin. However, reaction velocity and conversion rate of POP2 are low, and its bioactivity has not been elucidated. Thus, we have established a new method for preparation of POP2 with a purity of 96.8%, and the inhibitory activity of POP2 on 3T3-L1 preadipocytes was investigated. POP2 decreased adipocyte viability and inhibited the accumulation of intracellular triglycerides (TG). Furthermore, POP2 suppressed transcription of fatty acid synthase (FAS) and glucose transporter 4 (GLUT-4), led to reduce lipid accumulation. Also, POP2 down-regulated transcription and expression of PPAR γ, C/EBPα, and FAS, led to inhibition of adipocyte differentiation. An efficient method to produce POP2 was developed, and we demonstrated that POP2 reduced lipid accretion. These results are useful for potential applications of phlorizin in the food and pharmaceutical industries.